UNINPAHU Institutional Repository, a platformfor conserving, preserving and sharing academicknowledge - Gerena Herrera, José Alexander (2026)
In the context of digital transformation, it is essential for educational institutions—especially in the field of higher education—to effectively manage knowledge and academic resources. The preservation and dissemination of knowledge are key aspects. To meet this need, UNINPAHU has launched an institutional repository using DSpace, an open-source software that simplifies the creation and management of digital collections. This repository allows for the storage of a wide range of data, including books, theses, photographs, videos, and research data. The main objective of this project is to establish UNINPAHU’s institutional repository in DSpace in order to centralize, preserve, and disseminate the academic and scientific output of the academic community. This initiative not only improves the institution’s visibility and online presence, but also facilitates efficient access to academic output for students, faculty, researchers, and the general public. A survey was conducted among members of UNINPAHU’s academic community, which showed the need to implement the institutional repository. Subsequently, after evaluating different options, DSpace was selected as the software to be used for the implementation of the institutional repository. Finally, an information architecture was applied that corresponds to the characteristics and meets the needs of the University. As a result of the project, the Institutional Repository was implemented.